PENGARUH BEBAN KERJA DAN WORKLIFE BALANCE TERHADAP STRES KERJA KARYAWAN PT. BANK DANAMON INDONESIA, TBK. CABANG GORONTALO - Paramata, Mohamad Rolli; Yakup, Yakup; Abdullah, Julie; Runtukahu, Resita Olivya (JURNAL DIMENSI, 2024)
This study aims to analyze the influence of workload and worklife balance on employee job stress at PT. Bank Danamon Indonesia, Tbk. Gorontalo Branch. The data used in this study were sourced from questionnaire responses. The population of the study consisted of 59 respondents using a census method. The analytical technique used was multiple regression analysis. The findings of this study are (1) workload has a positive and significant effect on job stress, (2) worklife balance has a positive and significant effect on job stress, (3) workload has a positive and significant effect on worklife balance.